Beveridge Report Sub-committee : agreed statement of conclusions
1943-03-18 1943 1940s 4 pages 3. We are opposed to the provision for bribing aged workers to remain in industry, after the age of sixty-five, by a rising scale of benefits. It is not in the interest of the nation that aged workers should displace younger ones: moreover, an obvious injustice would arise, favouring men and women in light jobs against those in hard physical labour or heavy industry. 4. The use of the term 'abnormal subsistence needs' and the fixing of a normal subsistence level at a point which needs assistance or voluntary additional insurance to provide decent standards of life (paragraph 193, Part 111 - Section 1) are unworthy of the spirit of the Report as a whole. Starvation must not be used as a whip. 5. To continue reliance on free meals and supplies of free or cheap milk (paragraph 232, Part 11 - Section 1) as part of a scheme of Social Security appears to us to be wrong in principle. It retains an atmosphere of charity and shifts responsibility from the parent. Family allowances may need safeguards against abuse by parents lacking a sense of social responsibility, but such allowances should continue until school leaving age and not cease at a fixed age, and should be adequate without the aid of free meals. One final word. The Report is a Social Document of great value. We support it and urge the study of its provisions upon all who have not already done so. 18/3/1943 [Handwritten inscription] Chairman, Employment Group 292/150.5/5/62